2013
DOI: 10.1111/j.1464-410x.2012.11683.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of the prostate cancer gene 3 (PCA3) urine assay in Japanese men undergoing prostate biopsy

Abstract: What's known on the subject? and What does the study add?• It is known that a prostate cancer gene 3 (PCA3) urine assay is superior to serum PSA level or PSA-related indices for predicting a positive biopsy result in European and US men.• This is the first report on PCA3 in a large cohort of Japanese men. The diagnostic value of the PCA3 score in Japanese men was similar to those reported in European and US men. The study concludes that a combination of PSA density and PCA3 score may be useful for selecting pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…A score of 35 is commonly accepted, whereas a score of 20-25 is used in some studies to increase the diagnostic sensitivity of the assay [23, 24]. Based on a PCA3-Score of 35, the assay has a sensitivity of 52-67%, a specificity of 72-80%, and a diagnostic accuracy of 70-77%, according to several estimates [25-28]. The highest (85%) diagnostic accuracy is achieved with PCA3-Score of 20, according to the most recent meta-analysis [29].…”
Section: Tmprss2:erg and Pca3 Expression In Primary Tumorsmentioning
confidence: 99%
“…A score of 35 is commonly accepted, whereas a score of 20-25 is used in some studies to increase the diagnostic sensitivity of the assay [23, 24]. Based on a PCA3-Score of 35, the assay has a sensitivity of 52-67%, a specificity of 72-80%, and a diagnostic accuracy of 70-77%, according to several estimates [25-28]. The highest (85%) diagnostic accuracy is achieved with PCA3-Score of 20, according to the most recent meta-analysis [29].…”
Section: Tmprss2:erg and Pca3 Expression In Primary Tumorsmentioning
confidence: 99%
“…The results were much better than those using PSA. The best PSA cutoff value showed only 57.4% and 53.8% sensitivity and specificity, respectively 10111213232425. In an American study, the diagnostic accuracy of the score was evaluated in men undergoing an initial biopsy (277) and a repeat biopsy (280) 26.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown a high level of PCA3 during the first biopsy. The sensitivity and specificity have been reported to be as high as 82.3% and 89.0%, respectively, with small differences 891011. However, these results differed in repeated biopsies.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have sug gested a positive relationship between increased urinary PCA3 score and prostate cancer grade. [34][35][36] To demonstrate the utility of urinary PCA3 levels in predicting aggressive ness of prostate cancer on analysis of the biopsy sample, van Poppel et al 33 pooled data from two multi centre European prospective studies, comprising clinical data from over 1,000 men. 34 The mean and median urinary PCA3 scores were lower in men with biopsy Gleason scores <7 versus those with Gleason scores ≥7, stage T1c versus cancer stage T2ac cancer, ≤33% versus >33% positive biopsy cores, and in those with 'biopsy indolent' versus 'biopsy significant' prostate cancer by Epstein defi nition.…”
Section: Key Pointsmentioning
confidence: 99%
“…Therefore, measure ment of urinary PCA3 improves the decisionmaking process and reduces the use of unnecessary repeat biopsy procedures (Table 3). 11,32,33 The ability to predict cancer grade and aggressive ness is, arguably, of equal importance as avoiding the unnecessary use of biopsy procedures. Diagnostic tools that enable active prediction of these characteristics would enable urologists to separate patients with clini cally relevant prostate cancer needing definitive treatment from those with indolent disease, who might be better served with active surveillance.…”
Section: Key Pointsmentioning
confidence: 99%